1998
DOI: 10.5144/0256-4947.1998.212
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Habits of King Saud University Students in Abha, Saudi Arabia

Abstract: Background:The aim of this study was to estimate the prevalence of smoking among university students of King Saud University in Abha City, to determine ecological factors for the problem, and to assess the students' knowledge about the health effects of smoking, and attitudes towards public action against smoking. Materials and Methods: All medical students at the University College of Medicine (MC) (n=202), and a representative sample of students of the College of Education (CE) (n=300), were subjected to a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
30
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 10 publications
9
30
5
Order By: Relevance
“…We have no explanation for the intermediate risk in students in the science schools. Similar findings were observed in a Saudi study in Abha that compared smoking between college of education and college of medicine students [15], and a Syrian study that found that the rate of smoking was lower among medical students [19].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We have no explanation for the intermediate risk in students in the science schools. Similar findings were observed in a Saudi study in Abha that compared smoking between college of education and college of medicine students [15], and a Syrian study that found that the rate of smoking was lower among medical students [19].…”
Section: Discussionsupporting
confidence: 70%
“…These figures are higher than the PCBS estimates of the proportion of smokers in the general Palestinian population which was 19.8% (37.0% among males and 2.2% among females) [8]. Compared with university students in Arab countries, our Palestinian students had a higher rate compared with Jordanian (28.6%) [14] and Saudi (17.5%) students [15] but lower than Lebanese (40%) students [16].…”
Section: Discussioncontrasting
confidence: 42%
“…For multivariate analysis, only types of faculty significantly influence the knowledge of the university students towards lung cancer (p=0.001). Medicine students had greater knowledge about lung cancer than did those in other specialties because of the emphasis of their curricula on health information, as was also noted by Abolfotouh et al [66].…”
Section: Discussionsupporting
confidence: 50%
“…This study shows that, smoking practice was more common in low and middle-income, and illiterate group which was reveled in other studies. [11][12][13][14][15][16][17] As the age increased, having higher education and economic stability, the impact of smoking prevalence might be fallen. This study showed in Figure 1 and 2 that the intensity of smoking has been decreasing with age and good economic status.…”
Section: Discussionmentioning
confidence: 99%